Estabilização de taludes em colúvio com o uso de cortinas ancoradas - Santos, Isadora Guimarães dos (2017)
Road and urban construction often requires the excavation of colluvium. Among stabilization actions for the remaining part of the mass, it is possible to mention deep drainage, (draining) weight berms and anchored walls. This paper explores the last solution, since it has, historically, presented recurring problems. There are several reports of collapses of anchored walls that had been designed as usual retaining walls, even when considering a relatively high water table position. Initially a review of available methods is presented. The shortcomings of a Brazilian wedge method are worked around (herein referred as “proposed method”). The study of a hypothetical case, which represents a typical Southeast region's situation, is carried out to compare different design methods. The effect of the presence of water flow in the mass is examined. The work also explores the partial excavation of the colluviums.